Interfacial contribution to thickness dependent in-plane anisotropic magnetoresistance - Tokaç, M.; Wang, M.; Jaiswal, Shashank; Rushforth, A.W.; Gallagher, B.L.; Atkinson, D.; Hindmarch, A.T. (AIP Publishing, 2015)
We have studied in-plane anisotropic magnetoresistance (AMR) in cobalt films with overlayers having designed electrically interface transparency. With an electrically opaque cobalt/overlayer interface, the AMR ratio is shown to vary in inverse proportion to the cobalt film thickness; an indication that in-plane AMR is a consequence of anisotropic scattering with both volume and interfacial contributions. The interface scattering anisotropy opposes the volume scattering contribution, causing the AMR ratio to diminish as the cobalt film thickness is reduced. An intrinsic interface effect explains the significantly reduced AMR ratio in ultra-thin films.